Exclusive Breast-Feeding Practice and Associated Factors among HIV-Positive Mothers in Governmental Health Facilities, Southern Ethiopia - Lewam Mebratu; Selamawit Mengesha; Yadessa Tegene; Abraham Alano; Alemayehu Toma (Journal of Nutrition and Metabolism)
Introduction. Globally, over 90% of HIV infections among children are due to mother-to-child transmission and breastfeeding accounts for 5–20% of the burden. Avoidance of inappropriate feeding practices and practicing exclusive breastfeeding is recommended to reduce mother-to-child HIV transmission, but it is hardly practiced. The aim of this study was to determine the prevalence of exclusive breastfeeding practice and associated factors among HIV-positive mothers attending governmental PMTCT clinics in Southern Ethiopia. Methods. An institution-based cross-sectional study was conducted from April to May 2019. The participants of the study were 209 HIV-positive mothers at the selected PMTCT sites. The study subjects were drawn from 10 health institutions located at 6 towns in Southern Ethiopia which constituted six hospitals and four health centers. Quantitative data were collected using the pretested structured questionnaire. Logistic regression analysis was used to determine the association between the predictors and outcome variable. Results. Among the 209 participants, 81.6% (95% CI: 75.8–86.5) practiced exclusive breastfeeding and 18.4% (95% CI: 13.5–23.7) practiced mixed feeding. Mothers who had attended the recommended four antenatal visits [AOR: 3.01, 95% CI (1.1–8.28)], who had disclosed their serostatus [AOR: 3.17, 95% CI (1.12–8.99)], who had sufficient knowledge about infant feeding practice [AOR: 3.32, 95% CI (1.15–9.55)], and favorable attitude towards infant feeding practice [AOR: 5.39, 95% CI (1.65–17.6)] were more likely to practice exclusive breastfeeding. Conclusion. Exclusive breastfeeding was predominantly practiced. But mixed feeding was also being practice considerably. Improving maternal knowledge and attitude towards appropriate infant feeding practice through appropriate counseling on ANC visits could significantly improve EBF practice. It was also evident that promoting disclose of serostatus could empower the mothers to make an informed decision on how to appropriately feed their newborn.